Breastfeeding (Rada'ah) under and Islamic law and it's promotion towards sustaining mother's and children's health - Mohd, Azizah (2011)
In general, breastfeeding refers to a process of milk feeding of babies from the breast of a woman. In Islam, breastfeeding is highly recommended where the duty lies with both parents. The father is duty bound to provide milk feeding as part of the duty to maintain his child while the mother is naturally and customarily duty bound to breastfeed her baby in the case where she encounters no problem. Parents are given the option to send their babies to a wet nurse (foster mother) for suckling purposes, if the mother encounters problems or is reluctant to breastfeed her baby herself. This paper seeks to examine the position and rules relating to breastfeeding under Islamic law and its promotion towards it in order to sustain the health of both mother and child. For that purpose, emphasis will be given on proofs and arguments on the importance and benefits of breastfeeding (rada’ah). Examination will also involve breastfeeding as one of the parental duties as well as the children’s rights. It is highly believed that the research will benefit all academicians, legal practitioners, students, those who seek knowledge and the public at large.